Whole Genome Association Study in a Homogenous Population in Shandong Peninsula of China Reveals JARID2 as a Susceptibility Gene for Schizophrenia. (23rd September 2009) - Liu, Yang; Chen, Gang; Norton, Nadine; Liu, Wenmin; Zhu, Haining; Zhou, Peng; Luan, Meng; Yang, Shulin; Chen, Xing; Carroll, Liam; Williams, Nigel M.; O'Donovan, Michael C.; et al.
Abstract : DNA pooling can provide an economic and efficient way to detect susceptibility loci to complex diseases. We carried out a genome screen with 400 microsatellite markers spaced at approximately 10 cm in two DNA pools consisting of 119 schizophrenia (SZ) patients and 119 controls recruited from a homogenous population in the Chang Le area of the Shandong peninsula of China. Association of D6S289, a dinucleotide repeat polymorphism in the JARID2 gene with SZ, was found and confirmed by individual genotyping (X 2 = 17.89 ;P = .047 ). In order to refine the signal, we genotyped 14 single nucleotide polymorphisms (SNPs) covering JARID2 and the neighboring gene, DNTBP1, in an extended sample of 309 cases and 309 controls from Shandong peninsula (including the samples from the pools). However, rs2235258 and rs9654600 in JARID2 showed association in allelic, genotypic and haplotypic tests with SZ patients from Chang Le area. This was not replicates in the extended sample, we conclude that JARID2 could be a susceptibility gene for SZ.